207k views
0 votes
-5 (1-5x) + 5 (-8x -2) = -4x -8x Sep by step

User Rianoc
by
6.2k points

2 Answers

1 vote
You are going to distribute

-5(1-5x)+5(-8x-2)=-4x-8x

(-5*1) (-5*-5x)+(5*-8x)(5*-2)=4x-8x

-5 + 25x - 40x - 10 = 4x - 8x

~ Combine Like Terms ~

-5 + ( 25x - 40x ) - 10 = 4x - 8x

-5 + (-15x) - 10 = (4x - 8x)

-5 + (-15x) - 10 = -4x


~ Combine -5 and -10 ~

-5 - 10 - 15x = -4x

5 - 15x = -4x

~ Add 15x to each side combine it with its like term on the other side of the equal sign ~

5 - 15x = -4x
+15x +15x
___________
5 = 11x


We are going to divide to get the variable by itself

5 = 11x
__________
11x 11x

Your answer is (5/11)=x or 0.45 (repeating)= x
They are both the same answer just different ways to write it




User Meloney
by
5.7k points
2 votes
-5 (1-5x) + 5 (-8x -2) = -4x -8x
(-5*1)+(-5*-5x)+(5*-8x)+(5*-2)= -4x-8x
-5+25x+-40x+-10= -4x-8x
-15+-15x=-12x
-15= 3x
X= -5
User Matthewfx
by
5.5k points